Avaliação funcional do sistema nervoso autónomo na artrite reumatóide. - J D Soares; M Ferreira; P Póvoa; J A da Silva; M J Santos; A G Carlos (Acta Médica Portuguesa, 1993)
Sympathetic and parasympathetic nervous system evaluation was performed in 21 patients with rheumatoid arthritis. Every patient had autonomic nervous system (ANS) dysfunction, the parasympathetic involvement being the most frequent. ANS dysfunction may explain some manifestations and may well be the expression of a larger neuropathic involvement with pathogenic implications.